Utilização de Markdown para elaboração de TCCs: concepção e experimento da ferramenta Limarka - Alexandre, Eduardo de Santana Medeiros (2017)
The subject of this work is the use of a lightweight markup language (Markdown) to write dissertations and theses according to the ABNT rules. This document shows the devel- opment of Limarka, a tool that makes possible to write dissertations and theses with a lightweight markup language, and a experiment involving ten students writing a proposal of dissertations or theses. The methodology used was unstructured interviews with qual- itative analysis. The objectives of this research are: implement a tool to make possible write dissertations and theses according to the ABNT rules and evaluate its usage. The main outcomes of this research comes from two sources: 1) knowledge acquired from the de- velopment of the application. They are: a dissertation or a thesis cannot be produced from a tool that uses the DocBook format as a intermediary format. The abnTeX communite makes available templates according to the ABNT rules. The use of a Latex templates based from abnTeX text. And the generation of Latex Code from Markdown texts. 2) knowledge acquired from the analysis of experiments. They are: For the configuration of the template, the use of PDF form instead of making YAML code. There are evidences that Markdown and Latex are equivalent, in capabilities, and users will find the usage of a lightweight markup language easier to learn and use than Latex. The main conclusion of this work is that it is possible to write a dissertation or a thesis using a lightweight markup and produce documents according to the ABNT rules.